2009
DOI: 10.5004/dwt.2009.842
|View full text |Cite
|
Sign up to set email alerts
|

Submerged microfiltration coupled with physcio-chemical processes as pretreatment to sea water desalination

Abstract: A B S T R AC TIn this study, the critical fl ux of the submerged membrane system was experimentally evaluated when it was used for seawater with and without pre-treatment. In this study, different processes such as fl occulation with ferric chloride (FeCl 3 ) and different doses of PAC adsorption were used as a pre-treatment. The pretreatment of fl occulant of 2 mg/L of FeCl 3 and adsorption with the dose of 1 g/L PAC showed an improvement in the critical fl ux from 5 L/m 2 .h to 6.7 L/m 2 .h and 13.3 L/m 2 .h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Since it was previously suggested that the combination of membrane fi ltration with an activated carbon pre-treatment could be a promising improvement of the fi ltration performance (especially concerning the removal of organic matter [6,7]) it was decided to technically explore this method as well, again without coagulation, as a comparable case for the stand-alone MF.…”
Section: Membranes In Drinking Andmentioning
confidence: 99%
“…Since it was previously suggested that the combination of membrane fi ltration with an activated carbon pre-treatment could be a promising improvement of the fi ltration performance (especially concerning the removal of organic matter [6,7]) it was decided to technically explore this method as well, again without coagulation, as a comparable case for the stand-alone MF.…”
Section: Membranes In Drinking Andmentioning
confidence: 99%
“…There are mainly three types of physical methods [Y. 47 ; 48 ], (1) Flow equalization: It is used to enhance the efficiency of secondary wastewater processes by flattening out operation characteristics like pollutants levels, temperature, and flow over a period [R. 49 ]. (2) Sedimentation: It is often known as settling, is the removal of particulate matter, grit in the primary settling basin, and the flow of chemicals when the chemical coagulation method is used [ 50 ].…”
Section: Treatment Technologiesmentioning
confidence: 99%
“…Electrodialysis is a process of electrochemical separation technique in which anions and cations are transported in an electric field across an ion exchange membrane [ 82 , 49 ]. Ions with positive charges are pushed to the cathode, and ions with negative charges are moved to the opposite side of the anode.…”
Section: Electrochemical Technologies For the Treatment Of Wastewatermentioning
confidence: 99%
“…Air sparging improved the filtration flux at lower suspension and at lower air velocities and this enhancement depended on the size of the particles (Hwang and Wu, 2009 A study showed that PAC pretreatment was more efficient than flocculation-coagulation pretreatment for the seawater in terms of MFI-UF and silt density index (Zhang et al, 2009e). Another research showed that the addition of PAC could reduce the impact of fouling effect of high algae due to seasonal variation of algae numbers in surface water (Kweon et al, 2009).…”
Section: Filtrationmentioning
confidence: 99%